Natural stibnite embedded in hierarchical porous carbon enhance electrochemical storage for lithium-ion batteries anode. (November 2021) - Yu, Juan; Wei, Yinbo; Meng, Bicheng; Wang, Lejie; Zhou, Lijiao; Yang, Naixing; Li, Linbo
Abstract: From the perspective of cost-effective, environmentally friendly, and process complexity, natural minerals are directly used in rechargeable battery electrode materials after beneficiation, which is more practical meaningful than chemical synthesis materials. However, natural minerals face the problem of material aggregation and pulverization as electrode materials, resulting in poor electrochemical performance. Herein, we successfully prepared mineral-derived anode material Sb2 S3 coated with hierarchical porous carbon for lithium-ion batteries. The stibnite particles are well distributed in the pores, which can effectively avoid the aggregation of stibnite particles and alleviate volume expansion. The Sb2 S3 @NHPC anode exhibits excellent cycling stability with reversible capacity of 600 mAh g −1 at 0.1 A g −1 after 50 cycles. This work offers an idea of preparing economical and eco-friendly lithium-ion battery electrode materials. Highlights: The Sb2 S3 @NHPC electrode materials were prepared. Natural stibnite is used as lithium-ion battery electrode material. Hierarchical porous carbon is prepared from hydrogel. Carbon coating and porous structure make stibnite obtain better cycling and rate performance.